The Effectiveness of Problem-Based Learning in Enhancing Students’ Explaining Competence on the Thermodynamics Topic - Sari, Siska Nilam; Zulkarnaen, Zulkarnaen; Hakim, Abdul; Efwinda, Shelly; Takebayashi, Tomohiro (Jurnal Pendidikan MIPA, 2025)
Scientific literacy, particularly the competence to explain phenomena scientifically, is an important skill for enabling students to apply scientific concepts to everyday contexts and participate in informed decision-making. This study explores the effectiveness of the Problem-Based Learning (PBL) model in enhancing students’ competence to explain scientific phenomena within the topic of thermodynamics, focusing on the cases of LPG and LNG. Using a quasi-experimental design with a pretest–posttest control group, participants were drawn from several public senior high schools in Samarinda, Indonesia, through cluster random sampling. The experimental group was taught using PBL supported by context-based student worksheets, while the control group received conventional, lecture-based instruction. The assessment instrument used essay questions aligned with six PISA indicators for explaining scientific phenomena, validated by experts, and confirmed to have high reliability. The findings show that students in the PBL group achieved greater improvement across all measured indicators compared to those in the conventional group. The most significant gains were observed in constructing and evaluating models, and in explaining the societal implications of scientific knowledge. These improvements were closely related to the structured stages of PBL, including problem orientation, organization of learning activities, guided investigation, development and presentation of solutions, and analysis and evaluation of the problem-solving process. Each stage fostered active engagement, collaborative discussion, the use of multiple representations, formulation and testing of hypotheses, and reflection on both process and outcome. The results suggest that PBL is effective for enhancing students’ scientific literacy, particularly in explaining competence by connecting abstract thermodynamic concepts with real-life contexts. This study supports the broader adoption of PBL as a strategy to strengthen critical thinking and scientific reasoning in line with Indonesia’s long-term educational objectives under the RPJPN 2025–2045 framework.    Keywords: problem-based learning, scientific literacy, thermodynamics, competence in explaining scientific phenomena.